Nonlinear electrostatic waves in the auroral plasma - Singh, S. V.; Rubia, R.; Devanandhan, S.; Lakhina, G. S. (My University, 2020)
Nonlinear electrostatic waves in a two-component magnetized plasma comprising of cold ions and suprathermal electrons following κ-distribution have been analyzed. The nonlinear electrostatic waves are considered to be propagating at an oblique direction to the ambient magnetic field. A parametric study of the effect of initial driving electric field amplitude (E0), wave Mach number (M), spectral index (κ), propagation angle (α) and ion drift velocity (δ) on the evolution and the existence domain of nonlinear electric field structures is carried out. The theoretical plasma model is able to generate electrostatic ion cyclotron and ion acoustic waves, with the variation in the initial driving electric field amplitude and Mach number. It is observed that with increase in the driving strength, the electric field structures evolve from sinusoidal to sawtooth to highly spiky bipolar waveforms. The presence of κ–electrons is perceived to reduce the initial driving strength required to generate spiky bipolar electric field structures as compared to Boltzmann-electrons. Further, the period of the waveforms were found to decrease with increase in κ. The electric field amplitude and the phase speed of the bipolar structures predicted by the theoretical model is found to be in the range of observed electric field and speed in auroral region by the FAST satellite.
Keywords: Spiky electric field structures; Auroral region; Suprathermal electrons